Comparison of Micronutrient Intake Among Students with and without Computer Vision Syndrome: Perbandingan Asupan Mikronutrien pada Mahasiswa dengan dan tanpa Computer Vision Syndrome - Nurfitri Bustamam; Nanang Nasrulloh; Pritha Maya Savitri; Panji Octo Prasetio (Amerta Nutrition, 2023)
Background: During the COVID-19 pandemic, the risk of computer vision syndrome (CVS) increased due to the prolonged use of digital devices. According to a study in 2018, the adult population in Indonesia suffered from micronutrient deficiency which is essential for the anatomy and physiology of the eye. Objectives: This study aims to compare the micronutrient intake among students with and without CVS. Methods: This study used a cross-sectional design. The data were collected online from 34 students of the Nutritional Science Program, Faculty of Health Sciences, Universitas Pembangunan Nasional “Veteran” Jakarta using 24-hour dietary recalls and questionnaires. The data collection was repeated four times. The diagnosis of CVS was established using the Computer Vision Syndrome Questionnaire (CVS-Q) which consists of 16 questions about the frequency and intensity of each symptom. The micronutrient intake was analyzed using an application, namely NutriSurvey 2007. A univariate analysis was carried out to describe the characteristics of the variables. An unpaired t-test or Mann-Whitney test was carried out to test the hypothesis about the difference in micronutrient intake between the non-CVS group and the CVS group. Results: From a total of 34 subjects, 22 subjects (64.7%) had CVS, most of whom suffered from micronutrient deficiency. The results showed no significant difference in subject characteristics and computer usage between the CVS group and the non-CVS group (p > 0.05). The two groups that showed no significant difference in micronutrient intake included Fe, Mg, Cu, vitamin E, vitamin A, retinol, vitamin C, and omega-3 (p > 0.05). However, the results of unpaired t-test showed a significant difference in Zn intake between the two groups (p = 0.036; CI = 0.125-2.716). Conclusions: Zn intake plays an important role in preventing CVS. Further research on the benefits of Zn supplementation in preventing CVS is necessary.